Oral health knowledge, attitudes, and practices of undergraduate students at a South African University of Technology - Mbele-Kokela, Feziwe Flora; Moodley, Rajeshree (South African Dental Journal, 2021)
Awareness of oral health is essential for developing healthy habits, and a correlation between improved knowledge and better oral health has been shown to exist. Health-related behaviours are more likely to be followed if a person has greater control over their health with a better understanding of diseases and their aetiology. To determine the knowledge, attitudes, and practices regarding oral health care among undergraduate students in the Life Sciences Department at a University of Technology, Free State. This descriptive study gives insights into the oral hygiene knowledge, attitudes, and practices of undergraduate students in the Faculty of Health and Environmental Sciences, Department of Life Sciences at a University of Technology. Data were collected using an online questionnaire eliciting quantitative and qualitative data. The results revealed that most of the participants, 80% (n=178) understood that oral health is essential to their overall wellbeing. Overall, in this research, the findings of oral health education were found not to be covered. However, we found that variations in the source of dental information were correlated with university students’ oral health behaviour. The study, therefore, concludes that oral health care knowledge, attitudes and practices are affected by education and show that advocacy for the promotion of oral health is significant for the students.